Risk factors for olfactory dysfunction in chronic rhinosinusitis - Mori, Eri; Matsuwaki, Yoshinori; Mitsuyama, Chieko; Okushi, Tetsushi; Nakajima, Tsuneya; Moriyama, Hiroshi (Auris, nasus, larynx, 2013)
Although risk factors for olfactory dysfunction in patients with chronic rhinosinusitis (CRS) have been examined, most studies did not distinguish between classified eosinophilic chronic rhinosinusitis (ECRS) and noneosinophilic chronic rhinosinusitis (NECRS). The incidence of eosinophilic disease in Japan differs from that in the West. Thus, when olfaction in CRS is investigated, ECRS and NECRS should be examined separately. In the present study, we examined the clinical characteristics associated with olfactory dysfunction in Japanese patients with ECRS and NECRS enrolled in a large multicenter, prospective cohort study. Olfactory examination results, demographic data, clinical factors, and comorbidity data were analyzed for 418 patients with CRS at 3 tertiary care centers. We used T&T olfactometry, intravenous olfactory test (the Alinamin test) and Likert scale to assess subjects’ olfactory function. Data were analyzed with univariate and multivariate analyses. Olfactory dysfunction was more severe and more prevalent in ECRS than in NECRS. We found that olfactory cleft polyps (odds ratio [OR], 3.24), ethmoid opacification (OR, 2.64), asthma (OR, 2.29), current smoking (OR, 1.74) and age ≥50 years (OR, 1.66) were associated with olfactory dysfunction in CRS. Ethmoid opacification (OR, 3.09) and olfactory cleft polyps (OR, 3.05) were associated with olfactory dysfunction in NECRS. Olfactory cleft polyps (OR, 3.98), current smoking (OR, 2.67), IgE ≥400IU/ml (OR, 2.65), ethmoid opacification (OR, 2.51), and asthma (OR, 2.34) were associated with olfactory dysfunction in ECRS. Olfactory dysfunction was more severe and prevalent in ECRS than in NECRS. Physician should pay attention to these clinical findings to diagnose olfactory dysfunction, especially in ECRS, and should provide appropriate explanation, guidance, and care. In addition, smokers should be advised to stop smoking to help prevent olfactory dysfunction.